A Robust System Integration for Autonomous Evacuation Navigation - Abu Samah, Khyrina Airin Fariza; Hussin, Burairah; Hasan Basari, Abd Samad (IOS Press, 2014)
During an emergency evacuation, there are two subsystems involved: fire alarm control panel system (FACPS) and building floor plan system (BFPS). Fire indicator in FACPS reacts as proactive fire notification. Once detected any abnormalities, it sends the signal to the system, and alarm will trigger continuously. Thereafter, emergency evacuations take into the place immediately, without providing any information on the location of the hazard. The second subsystem, BFPS has to follow the standards regulation as visual static emergency navigation. However, in reality, it does not help the occupants to navigate out of the building towards the safest route. At present, both systems operate independently with specific functions, but based on logic thinking; it should be linked to each other. This argument is referring to the actual scenario in the event of fire; FACPS causes the disruption of the original BFPS. Consequently, this gap has led the evacuation process become more complex and challenging, especially for unfamiliar occupant. Therefore, this study proposed robust system integration for autonomous evacuation navigation (AEN) by integrates both systems, and adapting systems thinking (ST) approach. System integration (SI) is a combination of systems into one coherent system, linked the components, and finally able to achieve its purpose and mission. On the other hand, ST supersedes SI and explores the full pattern of the subsystem behavior, interrelate each other, and provide the outcome. As a result, it manages to eliminate human as an agent and non-compliance problem. At the meantime, FACPS provides the location of hazard as an input for BFPS. Through dynamic approach, floor plan layout system updates and blocks the hazardous location simultaneously. Finally, it provides a dynamic navigation to solve wayfinding problem, especially for unfamiliar occupants towards the safe and shortest route.